HLA-based real time distributed simulation of a marine port for training purposes. (2013) - Massei, Marina; Tremori, Alberto; Poggi, Simonluca; Nicoletti, Letizia
The research proposes critical issues related to cooperative training in a synthetic environment based on a federation of simulators operating in the same virtual world. The authors propose a real-time distributed simulation called ST-VP (simulation team virtual port simulator), for training purposes that is able to take safety and operative efficiency also into account. The simulators, installed on low-cost training workstations, cooperate and share the same virtual environment based on the high level architecture standard for distributed simulation (HLA). With this approach, it is possible to apply distributed simulation to a relevant number of entities and proceed with low-cost training sessions in cooperative operations in intermodal terminals.